The Wade Case: An analysis - Fullarton, Lex; Pinto, Dale (2021)
The Australian Taxation Office (ATO) considers ALL animals sold as part of a primary production business as trading stock. However, the word ALL is not contained in s 995 of the Income Tax Assessment Act 1997 (Cth) (ITAA 1997); rather, the ATO view is based on its interpretation of the findings in Federal Commissioner of Taxation v Wade (‘Wade Case’).